ALIH AKSARA DAN ALIH BAHASA TEKS KITAB TAUHID DAN TASAWUF - Iftah Husniyati; Zulfadhli Zulfahdli (Faculty of Languages and Arts, Universitas Negeri Padang, 2019)
The method used in this research is adjusted to the stage of the research. At the data collection stage using descriptive methods. At the script transfer stage using the transfer method and the language transfer stage uses the language transfer method. There are 3 results of this study, namely (a) present the description of the script Kitab Tauhid dan Tasawuf (b) present the transfer of text Kitab Tauhid dan Tasawuf (c) present the transfer of the language of the text Kitab Tauhid dan Tasawuf adjusted to EBI. This text is that which contains the values in the Islamic religion. At the beginning of the text of the manuscript contains about monotheism that God is one. In this text also describes the attributes of God that are not owned by other creatures. Besides that in this text there is also a pillar of prayer that is true according to the teachings of Islam.